2013
DOI: 10.1103/physrevb.87.035114
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement, fractional magnetization, and long-range interactions

Abstract: Based on the theory of matrix product states, we give precise statements and complete analytical proofs of the following claim: A large fractionalization in the magnetization or the need of long-range interactions imply large entanglement in the state of a quantum spin chain.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
(49 reference statements)
3
15
1
Order By: Relevance
“…This result is in contradiction with the theorem proved in [17], the reason is that the ground state of our longrange hamiltonian does not necessarily related to the ground state of any short-range hamiltonian! This is simply because if it was possible to approximate the ground state of our hamiltonian with ground state of a short-range hamiltonian we would expect conformal symmetry which is not the case in our model.…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…This result is in contradiction with the theorem proved in [17], the reason is that the ground state of our longrange hamiltonian does not necessarily related to the ground state of any short-range hamiltonian! This is simply because if it was possible to approximate the ground state of our hamiltonian with ground state of a short-range hamiltonian we would expect conformal symmetry which is not the case in our model.…”
contrasting
confidence: 54%
“…In particular they found that the area law should be valid in higher dimensions even for long-range interacting harmonic oscillators, and most recently the entanglement entropy for the long range anti-ferromagnetic Ising chain is calculated by numerical means [16]. Finally we should mention that in [17] based on the matrix product states it was argued that for those long-range systems that do not have any short-range counterparts, in other words one can not approximate the ground state of the long-range model with the ground state of another shortrange model, the presence of the long-range interaction implies larger entanglement entropy or the volume scaling of the entropy.…”
mentioning
confidence: 99%
“…We proceed with the Eq. (22). To evaluate this integral we must consider B ∈ (−∞ < z < 0) ∪ (l < z < ∞) as the complement of the sub-region l. The matrix Λ becomes:…”
Section: Von Neumann and Rényi Entanglement Entropymentioning
confidence: 99%
“…While dipolar interactions did not destroy the SPT phases in our example, quantum magnets with long-range interactions have recently been shown to harbor unusual and often dimension-specific physics. [90][91][92][93][94][95][96] The polar-molecule experiment we propose could therefore help guide the theoretical understanding of these effects in two-dimensional and threedimensional systems, including SPT phases, where efficient numerical methods are lacking. In fact, the classification of SPT phases is yet to be extended to models with long-range interactions.…”
mentioning
confidence: 99%